Greenland, junction of Kejser Franz Joseph and Kjerulf Fjords - Boyd, Louise Arner, 1887-1972 (1931)
Kjerulfs-Dickson Fjords [Kjerulf and Dicksons Fjords]. In foreground Hisinger Glacier [Hisinger Gletscher] taken from south side above Dickson Fiord [Dicksons Fjord]. In background, on left, 'J.F.B.' Mt. [Mountain] on west side of Left Valley and also looks through Left Valley - In background - Right Valley (north side) also west side of Main Valley.